RISIKO LIKUIDITAS DAN DETERMINANNYA: STUDI EMPIRIS PADA BANK SWASTA NASIONAL DEVISA DI INDONESIA - Perminas Pangeran (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this study is to examine the influence of bank’s characteristics on liquidity risk in the case of 22 out of 35 commercial banks in Indonesia, by using data in the period 2010- 2015. The results show some important things. First, Capitalization has a positive effect on liquidity risk. Second, cash reserves and loan to deposit ratio also negatively affect liquidity risk. These results are supported by both proxies for liquidity risk, i.e. liquid assets to total assets and liquid assets to customer deposits and short-term funding. Third, the fifth characteristics of other banks, namely non-performing loans, size, profitability, loss loan reserve, no effect on liquidity risk.